Full-Endoscopic Soft Tissue Approach for Lumbar Disc Herniation - Walid Abouzeid (Egyptian Spine Association, 2016)
Background Data: Open lumbar microdiscectomy has been considered the gold standard in the management of lumbar disc herniation (LDH) because of its favorable outcomes in long-term follow up. Nowadays, minimally invasive discectomy is gaining recognition due to its advantages. The advantages endoscopic lumbar discectomy includes clear visualization, less injury to the paraspinal muscle, protection of spinal stiffness and dynamic structure better cosmetic effect, and less postoperative symptoms and open surgeryrelated complications with subsequent earlier return to work. Purpose: This study was conducted to evaluate the efficacy of transforaminal and interlaminar endoscopic lumbar discectomy in the treatment of lumbar disc prolapse. Study Design: A prospective descriptive case series study. Patients and Methods: A prospective descriptive case series study was carried out on 42 patients who had lumbar disc herniation not responding to medical treatment for 6 months. Patients included from those attending the neurosurgical department of Alexandria University, Sohag University Hospital, and Menonfya University; in the period from January 2012 to February 2015. All patients underwent either transforaminal or interlaminar endoscopic lumbar discectomy. Results: All patients had significant improvement in VAS score. According to Mac Nab's criteria; 79% of patients have excellent results and 11% have good results; thus giving about 90% satisfactory outcome. Out of the 25 patients undergone interlaminar approach, 24 (96%) had completed the planned operative procedure. On the other hand, out of the 17 patients who undergone transforaminal approach; only 12 patients (70.6%) had completed the planned operative procedure. Conclusion: Pure endoscopic discectomy is an effective surgical method for treatment of lumbar discprolapse. (2016ESJ104)